Steady-state distributed modeling of dissolved oxygen in data-poor, sewage dominated river systems using drainage networks. (January 2019) - Pilotti, Marco; Chapra, Steven C.; Valerio, Giulia
Abstract: The determination of water quality along a river drainage network is of paramount importance for many environmental applications. Whereas several codes have been proposed to deal with this problem along a single reach of a river, no simple solution has been proposed for a complex river network. In this contribution, a methodology is presented for preliminary screening of river water quality at the watershed-scale and at steady state. The solution process exploits the information contained within the watershed's space-filling drainage network ( SFDN ), that is automatically computed by processing the raster map of the watershed's elevations. To this end, a visiting algorithm for non-binary trees is coupled to a Newton-Raphson method that locally solves the system of nonlinear water-quality mass balances. We believe that the resulting framework will be especially valuable for initial screening analyses in data-poor watersheds. A free code called Q2T that implements the described methods is provided. Highlights: A simple distributed model for dissolved oxygen dynamics along a river network is presented. The model is suitable for preliminary screening at the watershed-scale and at steady state. A free code called Q2T that implements the described methods is provided.